Tuning mass of internal flexible wall to reduce seismic demand on exterior walls of liquid storage tanks. (15th October 2015) - Mousavi, J.; Tariverdilo, S.
Highlights: The paper investigates the effect of flexibility of internal wall in liquid storage tanks on the seismic demand of external rigid walls. It is shown that when the flexibility of the internal wall leads to substantial increase in the seismic demand by tuning the mass of internal flexible wall, it is possible to reduce the seismic demand including moment and shear on the external walls. Abstract: This paper investigates the possibility of tuning internal walls of rectangular water storage tanks to reduce seismic demand on the tank external walls. Derivation of the response of the coupled system including rigid external walls, flexible internal wall and fluid field is in frequency domain. Response of the tank is evaluated for different kinds of ground motion records, including near-source and long-period far-field records. It is shown that when the flexibility of the internal wall leads to substantial increase in seismic demand, by tuning the mass of internal flexible wall, it is possible to reduce the seismic demand on the external walls.